Body, culture and education. An hermeneutical perspective - Núria Castro-Lemus, Jordi Planella Ribera, Antonio Almeida, (Opción, 2019)
In this article we review the ways in which bodies interact with pedagogic discourse and praxis. We have looked, through hermeneutic pedagogy, at the forms of concealment and emancipation of student’s bodies. Moving on from the original idea, that learner’s bodies have been habitually objectified; it is possible to speak of embodiment or of the subjectivity of bodies, using a hermeneutic approach.